2009
DOI: 10.1371/journal.pone.0005628
|View full text |Cite
|
Sign up to set email alerts
|

Anode Biofilm Transcriptomics Reveals Outer Surface Components Essential for High Density Current Production in Geobacter sulfurreducens Fuel Cells

Abstract: The mechanisms by which Geobacter sulfurreducens transfers electrons through relatively thick (>50 µm) biofilms to electrodes acting as a sole electron acceptor were investigated. Biofilms of Geobacter sulfurreducens were grown either in flow-through systems with graphite anodes as the electron acceptor or on the same graphite surface, but with fumarate as the sole electron acceptor. Fumarate-grown biofilms were not immediately capable of significant current production, suggesting substantial physiological dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
466
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(505 citation statements)
references
References 50 publications
36
466
2
1
Order By: Relevance
“…This was similar to the previous studies that have reported the enrichment of Geobacter species in aquifer sediments by the addition of humics and other extracellular quinones [43]. The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45].…”
Section: Discussionsupporting
confidence: 88%
“…This was similar to the previous studies that have reported the enrichment of Geobacter species in aquifer sediments by the addition of humics and other extracellular quinones [43]. The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45].…”
Section: Discussionsupporting
confidence: 88%
“…As previously reported (Franks et al, 2009), the biofilm covered the entire available graphite anode surface and formed pillar-structured biofilms greater than 50 mm thick (Figures 2a and 3a). Although a low shear and turbulence forces due to a low flow rate may have favored a more complex biofilm structure, this biofilm structure was similar to those observed in a diversity of other microbial fuel cell designs (Reguera et al, 2006;Nevin et al, 2009), suggesting that the flow of medium through the fuel cell did not alter typical biofilm morphology.…”
Section: Resultssupporting
confidence: 60%
“…For example, a previous comparison between gene expression in G. sulfurreducens biofilms producing current versus biofilms growing on the same surface material, but using fumarate as the electron acceptor , revealed increased expression of the gene for PilA, the structural protein for the pili that seem to be electrically conductive pili (Reguera et al, 2005) and may be involved in electron transfer through anode biofilms (Reguera et al, 2006;Nevin et al, 2009). Cells in the inner and outer portions of the biofilm did not have a significant difference in pilA expression, but the adjacent gene, GSU1497, was less expressed (2.6-fold) in the outer biofilm .…”
Section: Transcriptional Analysis Of Outer Versus Inner Members Of Cumentioning
confidence: 99%
“…Gene deletion studies have suggested that the outer membrane surface c-type cytochrome OmcZ (GSU2076) is important for growth on current-harvesting anodes (Inoue et al, 2010Nevin et al, 2009;Richter et al, 2009). omcZ was upregulated during growth on Mn(IV) oxide but not Fe(III) oxide (Table 4).…”
Section: Anaerobic Respiration Of Insoluble Metal Oxidesmentioning
confidence: 99%